2012
DOI: 10.1152/ajpcell.00408.2011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypoxia and VEGF differentially modulate abundance and organization of myosin heavy chain isoforms in fetal and adult ovine arteries

Abstract: Hubbell MC, Semotiuk AJ, Thorpe RB, Adeoye OO, Butler SM, Williams JM, Khorram O, Pearce WJ. Chronic hypoxia and VEGF differentially modulate abundance and organization of myosin heavy chain isoforms in fetal and adult ovine arteries. Am J Physiol Cell Physiol 303: C1090 -C1103, 2012. First published September 19, 2012 doi:10.1152/ajpcell.00408.2011.-Chronic hypoxia increases vascular endothelial growth factor (VEGF) and thereby promotes angiogenesis. The present study explores the hypothesis that hypoxic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 72 publications
(118 reference statements)
3
36
0
Order By: Relevance
“…Hypoxic increases in MLC 20 abundance also might result from increases in translation efficiency, but available evidence suggests only inhibition of translation by hypoxia (33). Hypoxic increases in MLC 20 might be explained by phenotypic transformation toward a synthetic phenotype, which is characteristic of hypoxia (21). Such a transformation would increase MLC 20 as a component of increased nonmuscle myosin heavy chain expression, which is induced by chronic hypoxia in fetal carotid arteries (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxic increases in MLC 20 abundance also might result from increases in translation efficiency, but available evidence suggests only inhibition of translation by hypoxia (33). Hypoxic increases in MLC 20 might be explained by phenotypic transformation toward a synthetic phenotype, which is characteristic of hypoxia (21). Such a transformation would increase MLC 20 as a component of increased nonmuscle myosin heavy chain expression, which is induced by chronic hypoxia in fetal carotid arteries (21).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic increases in MLC 20 might be explained by phenotypic transformation toward a synthetic phenotype, which is characteristic of hypoxia (21). Such a transformation would increase MLC 20 as a component of increased nonmuscle myosin heavy chain expression, which is induced by chronic hypoxia in fetal carotid arteries (21). In light of evidence that hypoxia can increase protein degradation (45), this mechanism might also contribute to hypoxic increases in MLC 20 abundance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), prolonged exposure to growth factors (e.g. VEGF) in the experimental models but also in atherosclerotic lesions [26,27]. This phenotypic modulation is usually accompanied by a loss of contractile function together with progressively impaired expression of cytoskeletal markers of maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the VEGF gene is mainly stimulated by hypoxia through mediation of hypoxia-inducible factors (HIF), and is upregulated in vascular smooth muscle cells and endothelial cells under hypoxic conditions (Hubbell et al, 2012;Adeoye et al, 2013;Pichon et al, 2013). Studies (Walter et al, 2001;Hanaoka et al, 2003;Dorward et al, 2007) have shown that circulating VEGF levels may significantly increase when sea level residents acutely ascend to a high altitude, and overproduction of VEGF in the lung attenuates the development of hypoxic pulmonary hypertension due to the protection of an endothelium-dependent function (Partovian et al, 2000;Louzier et al, 2003;Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%